(untitled) (DAPesquisa, 2020)
This article is driven by the question “what are the ways of writing practice?”. From this question we investigate, through a careful listening and a welcoming practice, the notion of fishing as a method itself. Writing the practice as a way of exercising the performativities of the encounters as a creative power: what is written happens in the bodies and, through them, being graphed, materializes themselves - artwork. A process that seeks the horizontality between the bodies and their moving knowledge is presented. Bodies that contain life, and in accepting, refusing and/or pinching the invitation, forms poetic, aesthetic and political networks. Writing as a practice of living bodies, living in the exercise of their possible performativities.